The Deviation Of Informed Consent Practices: Understanding The Inspanning Verbintenis And Legal Aspects - Anang Riyan Ramadianto (Jurnal Ilmiah Dunia Hukum, 2023)
This research has the main purpose to determine the legal protection of patients on the deviation of informed consent practices concerned in Inspanning Verbintenis and legal aspects. This article emphasizes normative juridical research with descriptive research specifications approach to understand the deviation that happened in medical field and the importance of Inspanning Verbintenis. This study used secondary data obtained from the literature and is described systematically from the Indonesian law, books, National and International journals, news, and previous research related to informed consent practices and the legal aspect. Previous research found that in specific cased a healthy patient, plastic surgery performed for aesthetic reasons is a Resultaat Verbintenis because it concentrates on the result in accordance with a certain arrangement made at the beginning between the doctor and the patient, namely the actual outcomes as anticipated. Hence, to avoid the deviation and missed conception, the Indonesian regulation system requires legal protection clearly. The planned consequence of the medical action may not be realized due to either Inspanning Verbintenis or Resultaat Verbintenis. Therefore, the goal of informed consent is to safeguard the patient against all medical procedures carried out without their knowledge.